2024
DOI: 10.1001/jamaoto.2023.4739
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Estrogen in the Development of Head and Neck Cancer

Christian Doll,
Elena Hofmann,
Robert Preissner
et al.

Abstract: ImportanceSex differences in head and neck cancer (HNC) incidence suggest a potential contribution of sex hormones.ObjectiveTo assess the role of exogenous estrogen exposure in the development of HNC in female patients.Design, Settings, and ParticipantsThis large multicenter cohort study using clinical records from the TriNetX real-world database included 20 years of data (through May 31, 2023) from 87 health care organizations. The TriNetX database was searched for medical records for female patients with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To the Editor We read with great interest the article from Doll et al This study showed that oral contraceptives (OCs) are associated with increased risk of head and neck cancer (HNC), while hormone replacement therapy (HRT) was associated with decreased risk of HNC. To further elucidate the findings and enhance the robustness of the conclusions, we would like to propose several recommendations for consideration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor We read with great interest the article from Doll et al This study showed that oral contraceptives (OCs) are associated with increased risk of head and neck cancer (HNC), while hormone replacement therapy (HRT) was associated with decreased risk of HNC. To further elucidate the findings and enhance the robustness of the conclusions, we would like to propose several recommendations for consideration.…”
mentioning
confidence: 99%
“…The authors did not explicitly deliberate the management of cases where individuals ceased HRT for personal reasons. Besides, the definition of OC/HRT user is unclear in the Methods section . We would like to know whether the authors define OC/HRT user by Anatomical Therapeutic Chemical code or documentation in medical records.…”
mentioning
confidence: 99%
“…In Reply We are pleased with the ongoing scientific discussion on the role of oral contraceptives (OCs) and hormone replacement therapy (HRT) in the development of head and neck cancer (HNC) . We have read with great interest 2 Letters to the Editor by Lin et al and Yang et al and would like to address the concerns raised.…”
mentioning
confidence: 99%
“…To the Editor We read with great interest the article by Doll et al regarding exogenous estrogen in the development of head and neck cancers. We appreciated the results of this cohort study that head and neck cancer prevalence may be higher in female patients taking oral contraceptives and lower in female patients taking hormone replacement therapy.…”
mentioning
confidence: 99%